Evaluation of Provenances for Seedling Growth and Biomass Attributes in Azadirachta indica A. Juss - Jain, Avinash; Dhar, Pranav (Indian Forester, 2008)
Fifteen provenances of Neem (Azadirachta indica A. Juss.) were selected from 12 agroclimatic zones of Central India (Madhya Pradesh, Chhattisgarh and Orissa) for the study. Phenotypically superior trees from each provenance were selected on the basis of morphological characteristics. Seeds from these superior trees were collected, depulped, washed and sown in nursery beds. The growth of seedlings after six months of seed sowing was measured including parameters like shoot length, collar diameter, length of tap root, number of leaves and number of tertiary roots. Above-ground, underground and total biomass of the seedlings were also measured including fresh weights of shoot, leaves, secondary roots and tap root. A suitability index was worked out on the basis of height, collar diameter and total biomass of the seedlings. On the basis of the relative suitability score, Sundergarh provenance was found as the most superior provenance, followed by Sihore, Bargi and Damoh.